Osvobodilni tisk za mladino - Jožef-Beg, Jožica (Jezik in slovstvo, 2011)
The national liberation press for youth, which was established on Slovene territory during the time of the national liberation struggle (1941-1945), had an important influence on the development of culture and national consciousness, as well as on the literary creativity of the youth who were included in the partisan movement at that time. The article, which was written on the basis of research of material in the Archives of the Republic of Slovenia, presents the significance, characteristics, editorial policy and circumstances of the emergence of the most important central youth publications with regional reprints, regional district publications and military youth publications, limiting its focus to the part of youth periodicals that, in addition to political-informative texts, also published literary texts.
Keywords: Slovene literature; slovenska književnost; mladinska književnost; young adult literature; periodika; letaki; brošure; okrožnice; narodna zavest; kulturna zavest; NOB; World War II in Yugoslavia